Not just for the sake of a report : enhancing corporate social responsibility reporting by involving stakeholders - Jantunen, Pirjo (2015)
The purpose of this study was to find out if it is possible to improve the case organisation’s corporate social responsibility reporting by involving stakeholders. The research was conducted as a case study in Helen Ltd, a Finnish energy utility, and it focuses on the stakeholder views of the case company.